Phytochemical of Piper essential oil and acute toxicity against Helicoverpa armigera (Lepidoptera: Noctuidae) - Dos Santos, Thais Lohaine Braga [UNESP]; Turchen, Leonardo Morais; Dall'oglio, Evandro Luiz; Butnariu, Alessandra Regina; Pereira, Mônica Josene Barbosa (Revista Brasileira de Ciencias Agrarias, 2017)
Plant essential oils have been recognized as important natural resources for bioprospection of new insecticides. Here, we provided a chemical analysis and assessing the toxicity of the essential oil of Piper aduncum L. (Piperaceae) against Helicoverpa armigera Hubner (Lepidoptera: Noctuidae) a cosmopolite and key pest in agricultural systems. The essential oil was obtained from the leaves of P. aduncum via hydrodistillation. Subsequently, acute mortality bioassays with two modes of exposure (ingestion and topical methods) were conducted to assess the lethal effects. The chromatograph analysis of P. aduncum essential oil indicated myristicin, isomyristicin, asaricim, dillapiole and isocroweacin the compounds more abundant. The acute toxicity bioassays exhibited concentration-dependent to mortality of larvae of first and third instar of H. armigera, when exposure by ingestion or topical application to Piper essential oil, with highlight to reduction in survival in 1st instar larvae. The median lethal time (LT50) when larvae were treated by ingestion was of LT50 < 14.20 days (first instar) and LT50 = 16.89 days (third instar). Whereas to larvae treated by topical method the median lethal time was of LT50 < 14.68 days (first instar) and LT50 < 10.73 days (third instar), which demonstrate a drastic reduction in survival of insect, when contrasted to control. In summary, our results highlight toxicity of P. aduncum essential oil against H. armigera and provide more information on plant-compounds that can be use in bioprospection of new insecticide molecules to pest management.
Keywords: Chemical-control; Pest-control; Phytoinsecticide; Piperaceae; Toxicology